2021
DOI: 10.3389/fbinf.2021.764497
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic AI Modeling and Pseudo Time Series Profiling of AD and PD Based on Individualized Serum Proteome Data

Abstract: Background: Parkinson’s disease (PD), Alzheimer’s disease (AD) are common neurodegenerative disease, while mild cognitive impairment (MCI) may be happened in the early stage of AD or PD. Blood biomarkers are considered to be less invasive, less cost and more convenient, and there is tremendous potential for the diagnosis and prediction of neurodegenerative diseases. As a recently mentioned field, artificial intelligence (AI) is often applied in biology and shows excellent results. In this article, we use AI to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Zhang et al constructed an ANN diagnostic model and confirmed that its accuracy, sensitivity, and specificity were 90%, 88.24%, and 90.91%, respectively. 13 Kriegeskorte et al identified benign and malignant thyroid nodules in 162 patients using DNN and ultrasonic images, with 96.34% accuracy, 86% sensitivity, and 99% specificity, respectively. 14 However, none of these methods were evaluated based on clinical practice, and some complex images required complex calculational analysis and lengthy processing times, so these methods are not suitable to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al constructed an ANN diagnostic model and confirmed that its accuracy, sensitivity, and specificity were 90%, 88.24%, and 90.91%, respectively. 13 Kriegeskorte et al identified benign and malignant thyroid nodules in 162 patients using DNN and ultrasonic images, with 96.34% accuracy, 86% sensitivity, and 99% specificity, respectively. 14 However, none of these methods were evaluated based on clinical practice, and some complex images required complex calculational analysis and lengthy processing times, so these methods are not suitable to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Jianhu Zhang et al [39] suggested working with blood biomarkers. As in the studies described above, feature selection was performed manually based on statistical data.…”
Section: Application Of Machine Learningmentioning
confidence: 99%